Combining ability for grain yield, agronomic traits and striga hermonthica resistance of yellow endosperm maize - Sangaré, Sekou; Menkir, A.; Ofori, K.; Gracen, V. (2018)
Maize production is constrained by Striga hermonthica in Mali leading to high yield losses. Breeding resistant hybrid maize is a promising alternative for increasing farmers’ income. The objective of this study was to evaluate the response of test crosses to Striga hermonthica and identify high yielding and adopted hybrid. Forty-five F1 hybrids and three checks were evaluated under Striga-infested and Striga-free conditions in Sanankoroba and Sotuba rainy season. Data collection was carried on grain yield, anthesis silking interval, plant aspect, plant height, days to 50% tasselling and silking, Striga damage ratings and Striga count at 8 and 10 weeks after planting. General combining ability (GCA) of line and Specific combining ability (SCA) of hybrids effects were significant for most traits under both conditions. GCA effects had greater proportion of variance than SCA effects suggesting additive gene effects controlling the inheritance of yield and Striga resistance. Parental lines TZISTR112, TZISTR1214, TZISTR1222, TZISTR1223, tester TZISTR1207 and TZISTR106 were the best combiner for grain yield under both conditions and they could be used in hybrid development.